2022
DOI: 10.3389/phrs.2022.1604775
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Air Pollution Leads to Adverse Birth Outcomes: A Systematized Review of Different Exposure Metrics and Health Effects in Newborns

Abstract: Objectives: To review the evidence of associations between adverse birth outcomes (ABO) and industrial air pollution.Methods: Searches were conducted in PubMed, and Scopus databases, and additional articles were found from snowball search techniques. The included studies feature a study population of mothers with live-born babies exposed to industrial air pollutants, and they examine the effects of industrial pollutants on adverse birth outcomes—namely, low birth weight, term low birth weight, preterm birth, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The current study showed a positive but statistically non-significant association between prenatal PM 10 exposure and ABOs, which is consistent with the existing evidence on non-significant association [ 72 , 74 ]. Despite the inconsistent results shown by earlier reviews [ 72 , 74 , 75 ], according to the recent review [ 26 ], a number of studies conducted in the ICS have shown a significant association between PM 10 and PTB [ 18 , 27 , 29 , 35 ] and LBW [ 27 , 29 , 32 , 33 , 53 ]. One of the reasons for the currently established non-significant association with PM 10 could be that the average annual concentration is on the borderline of the recommended air quality guideline by WHO [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study showed a positive but statistically non-significant association between prenatal PM 10 exposure and ABOs, which is consistent with the existing evidence on non-significant association [ 72 , 74 ]. Despite the inconsistent results shown by earlier reviews [ 72 , 74 , 75 ], according to the recent review [ 26 ], a number of studies conducted in the ICS have shown a significant association between PM 10 and PTB [ 18 , 27 , 29 , 35 ] and LBW [ 27 , 29 , 32 , 33 , 53 ]. One of the reasons for the currently established non-significant association with PM 10 could be that the average annual concentration is on the borderline of the recommended air quality guideline by WHO [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of BaP is seen only in LBW in Ida-Viru ICS; thus, the observed relations with air pollution may be coming from other unmeasured pollutants or a mixture of multiple pollutants as well, for instance, PAHs has shown even a strong effect on ABOs as suggested by systematized evidence [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, elevated levels of mercury or manganese in the blood of pregnant women have been associated with lower birth weight [2,3], increased maternal blood levels of lead with a higher incidence of preterm birth [4], and too high maternal lead and arsenic blood levels with a low Apgar score [5,6]. Pregnant women are particularly at risk of exposure to these and other heavy metals in low-and middle-income countries, where policies, legislation, and monitoring of residues in agricultural and industrial substances are insufficient [7,8]. This is also a concern in the Republic of Suriname, an independent country located on the northeastern coast of South America.…”
Section: Introductionmentioning
confidence: 99%
“…What's more, foetuses and infants are more susceptible to the effects of environmental pollutant than adults (Yi et al 2022). One of the important health risks of maternal exposure to air pollution during pregnancy is a variety of adverse birth outcomes (Balidemaj et al 2022;Flanagan et al 2022;Veber et al 2022).…”
Section: Introductionmentioning
confidence: 99%